OPTIMALISASI WAKTU REPARASI ZONA LAMBUNG DI BAWAH GARIS AIR - Wiliam Alexio Sagala (2022)
One of the problems that occur in the process of repairing the hull zone below the waterline on the ship has obstacles that cause the process to be slow due to the level of difficulty in the process and requires adequate facilities and equipment as well as the right process so that it can overcome the problems that occur. perform periodic or periodic repairs, the ship repair process takes a long time, there are often delays in the completion of ship repairs based on optimizing the repair time, solutions are needed to avoid delays in the repair of the hull zone below the waterline in the future. Research This aims to optimize repair time below the waterline. The methods used are crashing method, field study and literature study. Can reduce the duration of the contract by adding workers who are not yet optimal for repair of the hull zone under gas. ris air. It can be seen from the results of this study that 33% more effective reducing work time by adding workers in optimizing the repair time for the hull zone below the waterline. Keyword : Optimization of time,Repair, The Hull Zone Below The Waterline